Strategi pengembangan perkebunan kelapa sawit di Provinsi Jambi - Wahyudi, Ari (Jurnal Paradigma Ekonomika, 2022)
This research is entitled "Strategy for the Development of Oil Palm Plantation in Jambi Province". This study aims to determine and analyze the oil palm commodity in Jambi Province, find out and analyze the level of specialization and localization of the oil palm commodity in Jambi Province as well as to recommend oil palm commodity development strategies in Jambi Province. The approach used is quantitative and qualitative approaches. The oil palm commodity based on area and production is a leading commodity, while based on labor, the oil palm commodity is not a leading commodity and based on the calculation of the competitiveness of the oil palm commodity in Jambi Province, it is below the average. The results of the calculation of LI for oil palm commodity in Jambi Province can be interpreted. It can be interpreted that the level of distribution of the oil palm commodity in Jambi Province is relatively unbalanced and concentrated in certain places. positive contribution to plantations in Jambi Province. The results of the SWOT analysis for oil palm commodity are obtained : Strength Oil palm plantations in Jambi Province are a leading commodity where Jambi Province is one of the centers for palm oil production, there is a large area of ​​land available because the character of agricultural land in Jambi Province is suitable for plantation crops, especially oil palm, Jambi Province is a province that specializes in oil palm commodities with a location tend to be agglomerated and support from Provincial and District Governments in the form of policies and programs: Weakness not optimal absorption of labor for oil palm plantation commodities, low productivity of oil palm plantation commodities, low attractiveness and investment carrying capacity. In addition, there are also issues of deforestation and social conflict because there are distortions in governance and implementation of regulations and added value and product diversification is not optimal yet it is still dominated by crude palm oil and simple derivative products (olein and stearin) and palm oil exports are still mostly in upstream products. Opportunity : Changes in the production share of 4 (four) major vegetable oils in the world, the implementation of the Chinese Government's policy of the B5 program and the ability of the Government of India to only be able to meet their needs of 30 percent of its vegetable oil, the stipulation of mandatory biodiesel policies in Indonesia to reach B-30 in 2025 and Government Policies Republic of Indonesia in developing the national upstream and downstream oil palm industry. Threat : Foreign policy in limiting imports of CPO and its derivative products from Indonesia, the issue of the assumption that local governments are politicizing licensing, so that oil palm plantation development permits are out of control, increase in import duties on CPO from 7.5 percent to 15 percent, and tax increases imports of RPO (refined palm oil) from 15 percent to 25 percent and price fluctuations for farmers and business actors because the palm oil industry in Jambi Province is still dominated by crude palm oil and simple derivative products and palm oil exports are still mostly in upstream products.